The Artificial Intelligence Knowledge on Digital Literacy of Teaching Competence Among Islamic Education Teachers - Zalisman, Zalisman (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study employs a quantitative methodology with a descriptive correlational design to explore the impact of Artificial Intelligence (AI) knowledge on digital literacy, teaching competence, and instructional innovation among Islamic Education (PAI) teachers in Riau Province, Indonesia. The study involves a population of 6,840 secondary school PAI teachers registered with the Directorate General of Islamic Education. A sample of 378 teachers was determined using Slovin’s formula and selected through accidental sampling during professional development events. Data were collected using a structured Google Form questionnaire featuring Likert-scale items measuring teachers’ AI knowledge, digital literacy, instructional competence, and innovation. A pilot test was conducted to ensure the validity and reliability of the instrument. Descriptive statistics were used to describe the variables, while inferential statistics, including linear and Multivariate regression analyses, were applied to determine the relationships among variables. The study highlights the significant influence of AI knowledge on improving digital competence and fostering innovative teaching practices among PAI teachers. The findings emphasize integrating AI into teacher training programs to support educational advancement in Islamic schools.